2022
DOI: 10.1161/jaha.122.025507
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics, Predictors, and Outcomes of Early mTOR Inhibitor Use After Heart Transplantation: Insights From the UNOS Database

Abstract: Background The clinical characteristics of mTOR (mammalian target of rapamycin) inhibitors use in heart transplant recipients and their outcomes have not been well described. Methods and Results We compared patients who received mTOR inhibitors within the first 2 years after heart transplantation to patients who did not by inquiring the United Network for Organ Sharing (UNOS) database between 2010 and 2018. The primary end point was all‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…These reinvigorated T cells can potentially lead to improved anti-tumor efficacy of T-VEC and potentially other type of cancer immunotherapies. In addition to previously reported benefits from studies that have suggested lower risk of certain malignancies, lower mortality, fewer cardiac allograft vasculopathy-related events, and lower risk of renal dysfunction with the use of mTORi 70 , this dual benefit of mTORi may hold significant promise in the context of cancer immunotherapy for SOT recipients. By unraveling the underlying mechanisms involved in T cell exhaustion, differentiation, and response to immunotherapy, we can better optimize treatment strategies and potentially improve patient outcomes.…”
Section: Discussionmentioning
confidence: 80%
“…These reinvigorated T cells can potentially lead to improved anti-tumor efficacy of T-VEC and potentially other type of cancer immunotherapies. In addition to previously reported benefits from studies that have suggested lower risk of certain malignancies, lower mortality, fewer cardiac allograft vasculopathy-related events, and lower risk of renal dysfunction with the use of mTORi 70 , this dual benefit of mTORi may hold significant promise in the context of cancer immunotherapy for SOT recipients. By unraveling the underlying mechanisms involved in T cell exhaustion, differentiation, and response to immunotherapy, we can better optimize treatment strategies and potentially improve patient outcomes.…”
Section: Discussionmentioning
confidence: 80%
“…However, it may be important to assess the mTOR activity of tumour cells before initiating mTOR inhibitor therapy. Although rapalogs are generally used to reduce the risk of tumours after transplantation [ 52 , 53 ], there is a new study from 2022 questioning the effectiveness of early conversion to mTOR inhibitor-based IS regimens in reducing tumour incidence [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…mTOR inhibitors have been proposed as an alternative immunosuppressive agent to decrease the onset or progression of CAV, but a recent retrospective review of showed increased rates of rejection and CAV in children treated with mTOR inhibitors, though the authors did not feel the association with CAV was likely to be causal. 23 Statin medications have been shown to slow the development of CAV in adult patients, and studies in pediatric heart recipients demonstrate safety and efficacy in lowering total cholesterol, triglyceride, and LDL levels. Data on the effectiveness of statins to delay CAV in pediatric heart patients are mixed.…”
Section: Ardiova Scul Ar Dis E a S Ementioning
confidence: 99%
“…The causes of CAV are poorly understood but likely include some combination of immune mechanisms (e.g., antibody‐mediated rejection) in addition to traditional nonimmune cardiac risk factors, including dyslipidemia, hypertension, diabetes, and obesity. mTOR inhibitors have been proposed as an alternative immunosuppressive agent to decrease the onset or progression of CAV, but a recent retrospective review of showed increased rates of rejection and CAV in children treated with mTOR inhibitors, though the authors did not feel the association with CAV was likely to be causal 23 . Statin medications have been shown to slow the development of CAV in adult patients, and studies in pediatric heart recipients demonstrate safety and efficacy in lowering total cholesterol, triglyceride, and LDL levels.…”
Section: Cardiovascular Diseasementioning
confidence: 99%